It's a team if you use "reply all"': An exploration of research teams in digital humanities environments. - Siemens, Lynne (Literary & Linguistic Computing, 2009)
Given that the nature of research work involves computers and a variety of skills and expertise, Digital Humanities researchers are working collaboratively within their institutions and with others nationally and internationally to undertake the research. This work typically involves the need to coordinate efforts between academics, undergraduate and graduate students, research assistants, computer programmers, librarians, and other individuals as well as the need to manage financial and other resources. Despite this use of collaboration, there has been little formal research on team development within this community. This article reports on a research project exploring the nature of Digital Humanities research teams. Drawing upon interviews with members of the community, a series of exemplary patterns and models of research collaboration are identified and outlined. Important themes include a definition of team which focuses on common tasks and outcomes as well as a need for responsibility and accountability to the team as a whole; elements of a successful team which include clear task definition and productive working relationships over the life of the project and beyond, a need for balance between digital and face-to-face communication and collaboration tools, and potential for more deliberate training in collaboration and team work. The article concludes with recommendations for the individual team members, project leaders, and teams.